Perceived dental treatment need among older Tanzanian adults - a cross-sectional study - Åstrøm Anne N; Kida Irene A (BMC, 2007)
Abstract Background Need perceptions for dental care play a key role as to whether people in general will seek dental care. The aim was to assess the prevalence of perceived need of problem based dental care, dental check-ups and any type of dental care. Guided by the conceptual model of Wilson and Cleary, the relationship of perceived need for dental care with socio-demographic characteristics, clinically defined dental problems and self-reported oral health outcomes was investigated. Partial prosthetic treatment need was estimated using a socio-dental approach. Method A cross-sectional survey was conducted in Pwani region and in Dar es Salaam in 2004/2005. Information from interviews and clinical examination became available for 511 urban and 520 rural adults (mean age 62.9 yr). Results 51.7% (95% CI 46.2, 57.0) urban and 62.5 % (95% CI 53.1, 70.9) rural inhabitants confirmed need for dental check-up, 42.9% (95% CI 36.9, 48.9) urban and 52.7% (95% CI 44.5, 60.6) rural subjects confirmed need for problem oriented care and 38.4% (95% CI 32.4, 44.6) urban versus 49.6% (95% CI 41.8, 57.4) rural residents reported need for any type of dental care. Binary and ordinal multiple logistic regression analyses revealed that adults who reported bad oral health and broken teeth were more likely to perceive need for dental care across the three outcome measures than their counterparts. Socio-demographic factors and clinically defined problems had less impact. Based on a normative and an integrated socio-dental approach respectively 39.5% and 4.7% were in need for partial dentures. Conclusion About half of the participants confirmed need for problem oriented care, dental check-ups and any type of dental care. Need perceptions were influenced by perceived oral health, clinically assessed oral problems and socio-demographic characteristics. Need estimates for partial denture was higher when based on clinical examination alone compared to an integrative socio-dental approach.